Comparison of the forms of treatment of Russian and hindi - Verma, Kiran Singh (Journal of Oriental Studies, 2016)
this article deals with the comparison of forms of address in russian and hindi. here we analyze the formal and informal forms of addressing in both the languages – how the elders and the youngsters are addressed in a family, how one addresses a relative, how one addresses a friend, a stranger, when one is more polite and formal and when informal. Forms and formulas of russian language and hindi have analyzed by us on the basis of such distinctive features as: acquainted – unacquainted, related – unrelated, polite – impolite, formal – informal, senior – junior. sometimes we have taken into account simultaneously two criteria – how a senior addresses his/her junior, or how a junior addresses his senior, or active and passive participants of conversation, i.e. interlocutors.